Perbandingan Laju Pertumbuhan Bibit Mangrove Jenis Rhizophora apiculata di Desa Paconne dan Desa Senga Selatan - Genaro Genaro (Universitas Muhammadiyah Luwuk, 2023)
This research aims to determine the comparison of growth rates of Rhizophora apiculata mangrove seedlings in Paconne Village and South Senga Village. This research was carried out from April to July 2022 in Paconne Village and South Senga Village, Luwu Regency. The samples used in this research were mangrove seeds of the Rhizophora apiculata type. The results of the research showed that the growth percentage in South Senga Village was 72%, the average stem diameter was 7.7 cm, the average stem height was 4.84 cm and the number of leaves was 2 pieces. Meanwhile, the growth percentage in Paconne Village is 60%, the average stem diameter is 7.0 cm, the average stem height is 3.02 cm and the number of leaves is 2 pieces. So the best percentage growth rate of mangrove seedlings is found in South Senga Village.